Robust Load Frequency Control of Power Systems Against Random Time-Delay Attacks - Xiahou, K. S.; Liu, Y.; Wu, Q. H. (IEEE transactions on smart grid, 2021)
This letter presents a perturbation estimation based robust load frequency control (LFC) scheme for power system subject to random time-delay attack. Perturbation term is defined to describe the measurement deviation caused by random time-delay attack. Besides, perturbation observer is designed to estimate the system perturbation. The load frequency controller is compensated based on the perturbation estimation to mitigate the random time-delay attack and ensure the stable operation of power system. Case studies are undertaken on a two-area LFC model to demonstrate the control performance of the scheme.